Narrative review on attitudes toward organ donation of undergraduate nurse students. Issue 1 (27th August 2019) - Tsubaki, Michihiro; Tougo, Shusuke; Kobayashi, Masahiro; Arakawa, Satoru; Yoshida, Kazunari
Abstract: Aim: We aimed at obtaining suggestions to increase the number of organ donations by conducting a meta‐analysis of researches on attitudes toward organ donation for nurse undergraduates around the world. Methods: We looked for documents published by April 2017 using CINAHL, MEDLINE, Japan Medical Abstract Society, CiNii, and PsycINFO. We searched for English and Japanese literature including all terms of "attitude", "students", "nursing", "Tissue and Organ Procurement", "organ donation". This study was carried out based on the Prisma Statement 2010. Results: As a result of the search, six CINAHLs, 45 MEDLINEs, seven Japan Medical Abstract Society articles were extracted, but no papers from CiNii and PsycINFO. We extracted and analyzed 21 original papers including contents of organ donation, targeting nurse undergraduates, which also excluding scale development.